Design and development of aircraft systems - Seabridge, A. G.; Moir, I. (John Wiley & Sons, 2020)
"Design and Development of Aircraft Systems, Third Edition is for people who want to understand how industry develops the customer requirement into a fully integrated, tested, and qualified product that is safe to fly and fit for purpose. This edition has been updated to take into account the growth of unmanned air vehicles, together with updates to all chapters to bring them in line with current design practice and technologies as taught on courses at BAE Systems and Cranfield, Bristol and Loughborough universities in the UK. Design and Development of Aircraft Systems, Third Edition has been written to be generic and not to describe any single process. It aims to complement other volumes in the Wiley Aerospace Series, in particular Aircraft Systems Third Edition and Civil Avionics Systems by the same authors, and will inform readers of the work that is carried out by engineers in the aerospace industry to produce innovative and challenging -- yet safe and reliable -- systems and aircraft"-- Provided by publisher.
Keywords: Airplanes -- Design and construction.; Aeronautics -- Systems engineering.; elektronické knihy; electronic books